Quality of Life During Recovery: The Role of Family Interaction and Self-Concept among Heads of Families Undergoing Drug Rehabilitation - Rasikhah Ula Qurrota Aina; Risda Rizkillah; Musthofa (Journal of Islamic Psychology and Behavioral Sciences, 2026)
Heads of families involved in drug abuse often experience a decline in quality of life influenced by various psychosocial and familial factors. This study aims to analyze the influence of head of family characteristics, family characteristics, family interactions, and self-concept on the quality of life of family heads undergoing drug rehabilitation at BNN Lido Bogor. A quantitative approach was employed, supported by qualitative insights. Data were collected through questionnaires completed by 36 respondents and in-depth interviews with eight participants. The research was conducted from March to May 2025, and data were analyzed using descriptive statistics, correlation tests, and regression analysis with SPSS 25.0. The results showed that the level of addiction was significantly and negatively correlated with self-concept (r = –0.395, p < 0.05) and quality of life (r = –0.380, p < 0.05). In contrast, self-concept was significantly and positively correlated with both family interaction and quality of life. Regression analysis revealed that family interaction in the guidance dimension (β = 0.601, p = 0.010) and self-concept in the family dimension (β = 0.379, p = 0.005) significantly influenced the quality of life of the heads of families, with the model explaining 77.4% of the variance (Adjusted R² = 0.774). These findings highlight the vital role of family dynamics and individual self-perception in shaping the rehabilitation outcomes of individuals struggling with drug abuse. Strengthening family interactions—particularly in the guidance dimension—and fostering a positive self-concept are essential strategies to enhance the quality of life of family heads during the rehabilitation process.